Effects of Farmers’ Facial Expression on Consumers’ Responses in Print Advertising of Local Food: The Moderating Role of Emotional Intelligence - Yumi Seo; Yeong Seon Kang (Journal of Food Quality)
In the context of ethical consumption, we examine the effects of farmers’ facial expression in print advertising on consumers’ responses to local food. Furthermore, we try to verify the moderating role of emotional intelligence (EI) on consumers’ responses to the advertising message strategy. The advertising message strategy that connects farmers and consumers is expected to create more favorable responses among consumers toward local food and its retailers. This study examines consumers’ responses (perceived product quality, trust, and a positive attitude toward the local food retailer) to three conditions of farmers’ facial expression in the advertisement (neutral facial expression, positive facial expression, and product only, with no portrait) across two levels of EI (low and high). We find that farmers’ positive facial expressions in the advertisements have the greatest positive effects on consumers’ perceived product quality, trust, and attitude toward the local food retailer under a high level of EI. Therefore, individuals with a high level of EI were more influenced by facial expressions in print advertising, whereas those with a low level of EI were less influenced by facial expressions in print advertising, and their responses were indifferent to whether the local food farmer had a neutral or a positive facial expression in print advertising. Our findings suggest that marketing practitioners consider personal characteristics such as EI in persuading local food consumers in target markets to implement strategies to promote local food purchase and consumption.